PENGARUH IKLAN INTERNET DAN ELECTRONIC WORD OF MOUTH (EWOM)TERHADAP MINAT BELI SITUS ONLINE SHOPEE PADA MAHASISWA DI FEB MANAJEMEN UNIVERSITAS ISLAM MALANG - Randy Farid Rachmawan; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to identify and analyze internet advertising and electronics by word of mouth on buying interest in the Shopee Online site for Students of the Faculty of Economics and Business, Malang Islamic University.This research is expected to be one of the references for other parties and can also be used as literature for further research by providing a form of information relating to the variables of internet advertising and electronic word of mouth on buying interest in shopee online shop sites. The sample in this study was the FEB students of the Islamic University of Malang in the 2015-2018 academic year who had known 93 online shopee advertisements. This type of research is an explanatory research type using a quantitative approach. The data sources used in this study are primary data. Data collection is done by distributing questionnaires. Analysis of the data used in this study using validity, reliability, normality, multicolinerity test, heteroscedasticity test, multiple linear regression, t test, f test and coefficient of determination The results showed that Internet Advertising and electronic word of mouth (EWOM) had a simultaneous effect on buying interest and Internet advertising and electronic word of mouth (EWOM) had a partial effect on buying interest. Keywords: Iklan Internet, EWOM, Buying Interest